Mothers’ knowledge about infant and young child feeding practices and their health impacts. - Fazal, Amaila; Lasi, Fahad; Khan, Saad Ahmed (International Journal of Endorsing Health Science Research, 2022)
Background: Breastfeeding has always been proven beneficial for infant and mother’s health in every era. Thus, the present study was conducted to assess mothers' infant and young child feeding practices in Karachi, Pakistan, and their knowledge about the health impacts on their children. Methodology: A cross-sectional survey-based study including 1200 mother-child pairs was conducted from March to November 2020. Mothers' knowledge toward indicators for assessing infant and young child feeding practices (IYCF) questionnaire was used and scored using a four-point Likert scale. Results: Out of the total, most of the females were un-educated (97%), and the majority of them belonged to the middle class (49%). It was also found that 96% of the mother had breastfed their child, and more interestingly, 35% breastfed their child for 2 years. Almost 82% of mothers preferred breastfeeding and considered it necessary for the child. It was found that females had excellent knowledge about the young child feeding practices and their health impacts (66%). Furthermore, mother age, marital status, socioeconomic status (SES), number of children, occupation, personal and family disease history were significantly associated with the knowledge level of the mothers (p<0.05). Conclusion: It was found that females had excellent knowledge about the young child feeding practices and their health impacts. Future research is recommended to compare mothers' knowledge regarding infant and young child feeding practices in different geographical areas and districts of Karachi.